2019
DOI: 10.3390/v11100960
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Fever: Integrating Current Knowledge with Technological Innovations to Identify Strategies for Controlling a Re-Emerging Virus

Abstract: Yellow fever virus (YFV) represents a re-emerging zoonotic pathogen, transmitted by mosquito vectors to humans from primate reservoirs. Sporadic outbreaks of YFV occur in endemic tropical regions, causing a viral hemorrhagic fever (VHF) associated with high mortality rates. Despite a highly effective vaccine, no antiviral treatments currently exist. Therefore, YFV represents a neglected tropical disease and is chronically understudied, with many aspects of YFV biology incompletely defined including host range,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 246 publications
(322 reference statements)
0
21
0
7
Order By: Relevance
“…YFV belongs to the genus Flavivirus, which includes the Dengue and Zika viruses. These viruses have a highly conserved NS5 whose interactions, if disrupted, result in the loss of viral replication, likely across all flaviviruses [4,15]. We have previously reported that AT-752 has a direct effect on dengue viral replication, and presumably YFV as well, by forming the intracellular active triphosphate AT-9010, which then inhibits the RdRp responsible for viral replication [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YFV belongs to the genus Flavivirus, which includes the Dengue and Zika viruses. These viruses have a highly conserved NS5 whose interactions, if disrupted, result in the loss of viral replication, likely across all flaviviruses [4,15]. We have previously reported that AT-752 has a direct effect on dengue viral replication, and presumably YFV as well, by forming the intracellular active triphosphate AT-9010, which then inhibits the RdRp responsible for viral replication [12].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this deadly virus is a threat in regions where the vaccine is under-utilized, resulting in unanticipated cases from outbreaks or emergence in areas that have previously not been affected 4 by the virus, as observed by the recent large outbreaks and YFV emergence in Brazil and several African countries [4,5] that have caused significant morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Yellow fever (YF) is a viral hemorrhagic disease caused by a zoonotic pathogen known as yellow fever virus (YFV) [1]. Yellow fever is considered a mosquito-borne disease that is mostly common in the tropical zones of South America and Africa [2].…”
Section: Introductionmentioning
confidence: 99%
“…Они поражают нервную систему, вызывая парезы, параличи и энцефалиты и, кроме того, часто проявляются симптомами геморрагических лихорадок. Наиболее известны сезонный клещевой энцефалит [6], лихорадка денге [7], желтая лихорадка [8], лихорадка Западного Нила [9] и др. Последнее время в связи с развитием туризма, миграционными процессами и активизацией деловых связей возникла проблема завозных случаев вирусных заболеваний из тропических и субтропических стран в неэндемичные районы, в том числе и в Россию [10,11].…”
Section: Introductionunclassified